Non-clinical development of pharmaceuticals using engineered animal models - Bolon, Brad (Henry Stewart Talks, 2009)
Engineered animals in drug development, Why we use them, How we generate them, How we characterize them, How we select which model to use, How we use them
Archived at 2021/02/25